Amalan sekolah cemerlang di Sekolah Berasrama Penuh dan Sekolah Menengah Kebangsaan Agama: Satu perbandingan - A. Ghani, Muhammad Faizal; Siraj, Saedah; Kassim, Radzuan; Kenayathulla, Husaina Banu; Marzuki, Shahril@Charil; Elham, Faisol (University of Malaya, 2013)
This article analyzes differences in the operation of school excellence practices in two types of the high achievement schools in Malaysia i.e. boarding schools and religious schools.In particular, this study aims to identify the differences between in the excellence school practices and school leadership in the two types of the high achievement schools.To achieve the research objectives, data were collected through questionnaires distributed to 180 boarding school teachers and 180 religious school teachers by applying the survey method. The questionnaire that was developed by Muhammad Faizal A. Ghani (2008) was used as this study’s instrument. The instrument addresses the following seven dimensions as contributing factors to the effectiveness of the schools i.e. professional leadership, conducive school environment, concentrate of teaching and learning, high expectations, continuous assessment, collaboration and cooperation between school and home,and the school as a learning organization. The data were analyzed using descriptive statistics such as percentage and inferential statistics i.e. Mann-Whitney U test.This study found that a significant difference exists between the boarding schools and the religious schools in practicing the following excellence school practices i.e. principal leadership when the score p=0.001, and conducive school environment (p=0.003). In fact, the practices were better implemented by communities in the boarding schools compared to the religious school communities.This is true when the ranking mean of boarding schools is higher than the score of religious schools. Meanwhile, the element of school is rich in data and information is also practiced differently in both boarding and religious schools when the score p=0.007. However, the element is implemented more effectively in religious schools than in boarding schools. In other words, there was no significant difference between the both boarding and religious schools in other excellence school practices i.e. concentrate on teaching and learning,high expectations, continuous assessment, collaboration between school and home, and the school as a learning organization when the score p>0.05. The study also found there was a significant difference between the both boarding and religious schools in practicing the style of principal leadership when the score p=0.001. In this case,the practice is implemented more effective by school principals in the boarding schools than the religious schools when the ranking mean score of the boarding schools is more than religious schools’. However,there was no significant difference between both boarding and religious schools in practicing the teacher leadership style when the score p=0.531. The main implication of this study is to show the important need of principals to improve their own skills and to develop methos to improve student achievement.